1997
DOI: 10.1091/mbc.8.12.2407
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Oct-1 from the Nuclear Peripheral Structure Induces the Cellular Aging-associated Collagenase Gene Expression

Abstract: The cellular aging-associated transcriptional repressor that we previously named as Orpheus was identical to Oct-1, a member of the POU domain family. Oct-1 represses the collagenase gene, one of the cellular aging-associated genes, by interacting with an AT-rich cis-element in the upstream of the gene in preimmortalized cells at earlier population-doubling levels and in immortalized cells. In these stages of cells, considerable fractions of the Oct-1 protein were prominently localized in the nuclear periphery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 49 publications
3
57
0
1
Order By: Relevance
“…The second group contains proteins that are not integral membrane components, but are concentrated mainly in the region of the nuclear lamina. These include germ cell-less (GCL), young arrest (YA), PP1 phosphatase, and the transcription factor Oct1 (Imai et al 1997;Liu and Wolfner 1998;Steen et al 2000;Cohen et al 2001). In most cases, the roles of these laminassociated proteins in nuclear assembly and other nuclear functions have not been determined.…”
Section: A Role For Lamins In Nuclear Envelope Assemblymentioning
confidence: 99%
“…The second group contains proteins that are not integral membrane components, but are concentrated mainly in the region of the nuclear lamina. These include germ cell-less (GCL), young arrest (YA), PP1 phosphatase, and the transcription factor Oct1 (Imai et al 1997;Liu and Wolfner 1998;Steen et al 2000;Cohen et al 2001). In most cases, the roles of these laminassociated proteins in nuclear assembly and other nuclear functions have not been determined.…”
Section: A Role For Lamins In Nuclear Envelope Assemblymentioning
confidence: 99%
“…It has been suggested that the inner nuclear envelope may represent a resting place for transcription factors, a platform that sequesters them away from chromatin, thus preventing transcriptional action on their targets (Heessen and Fornerod, 2007). According to this hypothesis, the dissociation of OCT1 from the nuclear envelope has been shown to be associated with collagenase gene up-regulation during the cell-aging process (Imai et al, 1997). On the other hand, two recent genome-wide localization studies revealed that the association with nuclear lamina was mostly characterized by a repressive chromatin environment, devoid of active histone marks and RNA polymerase II binding activities (Pickersgill et al, 2006;Guelen et al, 2008).…”
Section: Subcellular Localization Of the Proteinmentioning
confidence: 99%
“…The POU-domain protein OCT-1 is associated with the nuclear lamina and represses the collagenase gene. Interestingly, in aging cells OCT-1 dissociates from the nuclear lamina allowing the activation of the collagenase gene [109]. Another transcription factor that is confined to the nuclear lamina is insulin promoter factor-1 (IPF-1)/ pancreatic and duodenal homeobox-1 (PDX-1) [110].…”
Section: Lamins In Transcription and Splicingmentioning
confidence: 99%